Polyester - El-Din Saleh, Hosam M. (IntechOpen, 2012)
Polyesters are being widely applied in different fields of life due to their excellent characteristics. A book "Polyester" comprises 16 chapters covering synthesis, characterization and applications of polyester. Chemical and biological methods for synthesis of polyester were one of the most important points of research added. Mechanical, physical, chemical characterizations and improvement of polyester were also explored. Some aspects of applications in immobilization of radioactive wastes, coating of aluminum alloys used in aircraft, fabrics manufacturing and the development of the new composites were covered, emphasising vast possibilities of implementation of that polymer. This book should serve as a support to many scientists, researchers and students as well as to other experts, both in academia and industry.